Academy Project to Start Soon - Gibson, Luther E., Sen. (Vallejo Times-Herald)
Work is about to be started on a new $800,000 engineering instruction building at the California Maritime Academy, the unit of the state college system which is located in Vallejo. The principal construction contract has just been let with contracts for site preparation and equipment expected very shortly.